Nghiên cứu ứng dụng công nghệ ozon để xử lý cao su phế thải thành dạng bột - Tuyên, Đỗ Ngọc; Thế, Ngô Kế; Hải, Lương Như; Minh, Đỗ Quang; Khải, Nguyễn Quang; Kháng, Đỗ Quang (Vietnam Journal of Chemistry, 2012)
Using gas with high content of ozone for destruction of waste rubbers is experimented in this paper. The factors that influence the treatment process were studied, such as: concentration and production of ozone, deformation and frequency of deformation on materials. The results show that with increasing of concentration and production of ozone (increasing capacity of ozone generator) the effect of process increases. The increasing ratio is nearly linear. When the power of ozone generator is constant, the ozone concentration increases while the production reduces or vice versa, the highest effect of process is achieved at an optimal point, which is where the concentration line and production line meet (on the chart of the specific lines of ozone generator VH40-135). When deformation of materials increases, the effect of process does too, almost linearly, but it gets optimum at the deformation frequency of 1.5 Hz.